KAJIAN SEMIOTIKA ROLAND BARTHERS DALAM MEMAKNAI TRADISI BALIAK SEDEKAH SUKU SERAWAI DI KECAMATAN SEMIDANG ALAS MARAS KABUPATEN SELUMA PROVINSI BENGKULU - Suardi, Himin; Ayuh, Eceh Trisna (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2024)
The Serawai tribe is an ethnic group with the second largest population living in the Bengkulu area. Like other ethnic groups, the Serawai Tribe in Seluma Regency has unique traditions that can still be seen today, including the tradition of baliak alms. The aim of this research is to analyze the meaning of the Serawai tribe's baliak alms tradition in Semidang Alas Maras District, Seluma Regency, Bengkulu Province. This type of research is field research. There were 4 informants, data collection through interviews, documentation and observation. Data analysis was carried out interactively and continued continuously until completion using Roland Barthes analysis. The findings of this research are that the implementation of the Serawai Tribe almsgiving tradition in Semidang Alas Maras District begins with the intention conveyed to the lebu/merajo/merajo lebu puun family that the party who will return to the lebu's house as a pilgrimage and at the same time hold a banquet. There are 3 symbols found in the baliak alms tradition, namely chicken, rice and juada bajik. The context of chicken has a denotative meaning of a type of poultry animal which is usually kept for use as meat, eggs and so on. White rice is rice that has its skin and white seeds removed and is a staple food source. Meanwhile, juada bajik is a traditional sticky food made from sticky rice, coconut milk and brown sugar, and tastes sweet and delicious. The connotation meaning of chicken symbolizes independence, responsibility and compassion. Then white rice symbolizes personality, prosperity and a sign of responsibility. Meanwhile, the diamond juada represents a symbol of love, compassion, and relationships that will always be sticky and close. The myth of the chicken in the baliak alms tradition is believed to be that from a young age the chicken looks for food and walks alone to guide its children. The hope is that children can be independent and their parents can be responsible and loving. Then the myth is that rice is believed to be able to meet needs. However, there is still hope that the child will have the character of humility and not be arrogant in the future. Meanwhile, in the juada virtuous myth, it is believed that children already have a life with their family, but they should strengthen the ties of friendship with their parents based on a relationship full of love and affection. Apart from symbols, the stages of event implementation also have denotational, connotative and mythical meanings. All these meanings reflect the Serawai people's concept of life Keywords : Baliak Alms Tradition, Serawai Tribe, Roland Barthes